An ideological clash of worldviews in State religious schools in Israel. (October 2019) - Elgad-Klonsky, Sari; Tamir, Eran
Highlights: We identify and map a culture war between progressives and conservatives in Israel's Zionist-religious public schools. Through a thick description of one case study, we illuminate the linkage of neo-liberalism and the rising power of parents in Zionist-religious public schools. Findings illuminate tensions around admission criteria in religious schools, based on religious observance, which seek to favor academic rigor and privileged social status. Abstract: This research examines the division of one religious-Zionist elementary public school in Israel. Led by the Parents' School Committee (PSC), discussions soon resulted in a fierce religious culture war between two groups of liberal and conservative parents who had two separate visions for the future of the school. Semi-structured interviews were conducted with prominent PSC members. Utilizing Bourdieu's concept of social field, interviews were analyzed to outline the culture war that divided the community and led to the foundation of a conservative school with gender separation and a liberal school with no gender separation for young children. Findings illuminate tensions around admission criteria in religious schools, based on religious observance, which seek to favor academic rigor and privileged social status.